(untitled) (Global Journal of Sciences, 2025)
This research aims to determine the approximate analytical solution of a one-dimensional time fractional-order cancer model using the homotopy perturbation method (HPM). Initially, the fractional derivative component which is in the Caputo sense converted into an integer order derivative by using the Laplace transform method, followed by the technique mentioned above. The tasted numerical examples illustrate the feasibility and reliability of the proposed approach with a fractional-order derivative. Additionally, the impact of the fractional order on the solution’s nature is analyzed graphically and numerically.